Research-oriented framework of training philology students⇔ research skills based on corpus analytical software - Valyukevych, Tetyana V.; Zinchenko, Olha Z.; Ishchenko, Yevhenii O.; Artemov, Volodymyr; Nechaiuk, Liudmyla G.; Артемов, Володимир Юрійович (Eurasian Society of Educational Research, 2021)
The purpose of the study was to explore how technological advances incorporated into the Philology Studies curriculum could impact the students’ research skills and the quality of their research projects and what students’ and teachers’ impressions of the reshaped research component of the curriculum were. The study used qualitative and quantitative methods with the dominance of qualitative methods. It employed the baseline study, checklist to assess students’ research papers, assessment criteria, and the Triangular Assessment Method to assess the students’ papers. The consensus meeting was held to allow the experts to express their reasoning for the scores. The semi-structured interview was administered to the students’ and teachers’ to identify their impressions of the reshaped research component of the curriculum of philology. The technological advances incorporated into Philology Studies curriculum improve the students’ research skills and the quality of their research projects. Both students and teachers appreciated the reshaped research component of the curriculum. The analytical software can be successfully incorporated in the corpus analysis-purpose student research. The students found the intervention a challenging experience that ‘pumped up’ their intellectual, research, and technical skills. They reported improvement in interpreting corpus using correlations, frequencies, distributions, and collecting information using software to organise it in a professional way. The lecturers agreed that the technology-based instructional model incorporated into Philology Studies curriculum improved both students’ research skills and the quality of their research projects. © 2021 The Author(s)
Keywords: Higher education; Research-oriented approach; Technologisation of the research-oriented approach; Tertiary students majoring in philology; Text-analysis-purpose software